Assessing Malaysian Preschool Children's Basic English Proficiency - Ahmad, Norlida; Ghazali, Munirah; Abdullah@Mustafa, Anna Christina; Ali, Amir Yazid (2004)
In Malaysia, students are required to learn the English language starting from Year One to Form Five. With eleven years of learning the language, students are expected to have attained a high level of proficiency in English. However, Malaysians' English language acquisition is still far from satisfactory even after years of exposure to English in a formal classroom setting. Alarmed by the decline of English proficiency amongst students, the Malaysian Ministry of Education decided that beginning 2003, English would be the language of instruction for mathematics and science subjects in primary and secondary schools, in the hope that English will be given the recognition it deserves in education. On the same note, the Ministry also decided that English be introduced to preschoolers. Therefore in Malaysia, preschool children are taught English so that they will be able to understand some instructions in the language when they are in Year One. This paper will discuss a study done to gauge the basic knowledge of 821 preschool children in English.